Behavioral Finance Factors and Investment Decisions in Retail: a Moderation Analysis Across Demographic Segments - Rita Satria; Nugraha Nugraha; Disman Disman; Imas Purnamasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Young retail investors in the Indonesian capital market often face challenges due to various behavioral finance biases that can negatively impact their investment decisions. This study aims to examine the impact of herding, overconfidence, mental accounting, loss aversion, and bias on the investment decisions of novice retail investors, focusing on the moderating role of demographic factors such as generation, gender, education, and income. Using a quantitative design, data were collected through a structured questionnaire from 254 retail investors, with 246 valid responses analyzed through a regression-based method and moderation analysis using Hayes' PROCESS macro for SPSS. The results indicate that all behavioral finance factors negatively impact investment decisions, with demographic variables significantly moderating this impact. The findings suggest that tailored financial education and advisory services can help young novice investors make more informed and rational investment choices, thereby improving their financial well-being and market participation. The limitations of this study lie in its focus on a specific demographic in Indonesia, while its novelty includes a detailed analysis of the moderating impact of demographics on behavioral finance biases.